2019
DOI: 10.3389/fevo.2019.00401
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia bavariensis: Vector Switch, Niche Invasion, and Geographical Spread of a Tick-Borne Bacterial Parasite

Abstract: The Borrelia burgdorferi sensu lato species complex currently consists of more than 20 species that utilize small vertebrate hosts as reservoirs and ticks of the genus Ixodes as vectors. The bacterial parasite species differ in their ecology (reservoir hosts, competent vectors) as well as geographical distribution. Several studies have defined reservoir host association as a driver for diversification, speciation and pattern of spatial occurrence of populations but in this review we focus on vector association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 161 publications
(219 reference statements)
3
60
1
Order By: Relevance
“…A good example of this is B. bavarensis, which was designated as its own species a few years back and not part of the B. garinii clade [86,87]. It is suggested that it diverged at some point from B. garinii, which is known to be bird-specific in terms of reservoir hosts and made a switch that enabled B. bavarensis to be associated with small mammals [5]. Genetic analysis is a valuable tool that has been employed extensively to determine important factors responsible for the pathogenesis of many bacterial species and could certainly answer questions regarding how genetic composition, including the identified CRASP genes, could lead to differences in reservoir host association [81,88].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A good example of this is B. bavarensis, which was designated as its own species a few years back and not part of the B. garinii clade [86,87]. It is suggested that it diverged at some point from B. garinii, which is known to be bird-specific in terms of reservoir hosts and made a switch that enabled B. bavarensis to be associated with small mammals [5]. Genetic analysis is a valuable tool that has been employed extensively to determine important factors responsible for the pathogenesis of many bacterial species and could certainly answer questions regarding how genetic composition, including the identified CRASP genes, could lead to differences in reservoir host association [81,88].…”
Section: Resultsmentioning
confidence: 99%
“…B. burgdorferi sensu lato complex (referred to as B. burgdorferi) comprises at least 20 named species [4,5], with most human Lyme cases in Europe being caused by B. burgdorferi ss, Borrelia afzelii, Borrelia garinii, Borrelia bavariensis and B. spielmanii [6]. In the USA, only B. burgdorferi ss and Borrelia mayonii [7] are commonly associated with human infection.…”
Section: B Burgdorferi Sensu Lato Complexitymentioning
confidence: 99%
“…However, the Russian isolates are new to the present paper and allow us to see that the Asian clade shows no detectable geographic clustering. Asian B. bavariensis are vectored by I. persulcatus, whereas the European vector is I. ricinus (see [9] for a review). As these two tick species co-occur and can even hybridize in their overlapping zone in Estonia, Latvia and Western Russia [56] , we expected that Russian B. bavariensis samples, might be genetically closer to the European isolates than the Japanese isolates, perhaps even showing that the European population might have diverged from a Russian lineage, but this was not the case.…”
Section: Discussionmentioning
confidence: 99%
“…7, 8 and 9) within or between the two B. bavariensis populations. Because all Asian B. bavariensis isolates are vectored by I. persulcatus, whereas European isolates are found only in I. ricinus, it has been hypothesized that it is the adaptation to a new vector species that caused the strong bottleneck observed in the European population (see [9] for a review). Genes that show a high differentiation between the two populations are particularly interesting candidates for playing a role in the adaptation to speci c tick vector species.…”
Section: Candidate Genes For Host and Vector Adaptation In B Bavariementioning
confidence: 99%
See 1 more Smart Citation